Avaliação de um programa de auxílio para alimentação de pacientes adultos hospitalizados - Garateguy, Denise Müller (2014)
Introduction: The administration of meals is not comprised to routinely assistance of nursing, being necessary to evaluate a volunteering program to help with these patients’ feeding. Objective: To compare the oral intake percentage of the hospitalized adult patient`s main meals submitted or not to an assistance program with qualified volunteers. Method: In an almost experimental clinical trial performed among hospitalized adults in a hospital from the metropolitan area from Porto Alegre City, between March and August/2014, the acceptance percentage of main meal intake (lunch) was evaluated between two groups of patients (a) with help from a volunteer to feeding and (b) without help from a volunteer to feeding, considering 100% when the patient ingested all the meal, 75% when the patient ingested ¾ of the meal, 50% when the patient ingested half the meal, 25% when the patient ingested ¼ of the meal and 0% when the patient did not ingest anything from the meal. Nutritional status was assessed by Body Mass Index (BMI) at admission and every seven days. The study was approved by Ethics Commitee of UNILASALLE/Canoas. Results: 90 individuals were included, 45 allocated in each group of evaluation. The average of age 67,5 ± 15,7 years, 46,7% was male. The BMI hospital admission average among the individuals was 20,4 ± 2,8, the BMI in the inclusion of the study was 19,6 ± 2,4 kg/m² for the group with help of qualified volunteers and 18,3 ± 2,5 kg/m² for the group without help of volunteers (p=0,018). When we reached the end of the study, that is, after 15 days, the BMI among the group with help was 20,3 ± 2,8 kg/m² and 18,9 ± 2,7 kg/m² for the group without help (p=0,024). In relation to food intake, both groups presented significant differences on the 9th day – the group with help of volunteers presented a median of 100% (50-100) and the group without help the median of 50% (12-100). On the 10th day the median among the group with help was 75% (37,5-100) and the group without help 50% (25-100). Among the reasons which patients remained nulla per os (NPO), most of them (61,1%) did not accept the meal offered and 29% were in therapeutic NPO. Conclusion: it was concluded that the help feeding program is able to improve the patients’ BMI on the 15th day of treatment. There was a significant improve in the food intake indexes on the 9th and 10th day of treatment among the patients who received help to feed themselves.